DISTRIBUTION OF YTTRIUM AND SOME OTHER TRACE ELEMENTS IN WIDE-SPREAD ACCESSORY MINERAL ASSEMBLEGES: TEMPERATURE DEPENDENCE AND ITS APPLICATION IN GEOCHEMICAL MODELING - Shnyukov, S.; Lazareva, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Yttrium, REE and some other trace elements distribution in accessory mineral assemblages including apatite (Ap), zircon (Zrn), monazite (Mnz), xenotime (Xnt), fluorite (Fl) were investigated. As a result, the Ap Zrn Y 1T ln K vs. (oK) dependence ( Ap Zrn Ap Zm K C C Y Y = ; Ap Zm Y Y C , C – Y Y content in apatite and zircon respectively) was preliminarily calibrated on the basis of host rock thermometry. Obtained equation y (6,8009 0,3270)x (7,1104 0,3133) = ±- ± ( ApZrn Y ln K y = , x 1000T = ) was applied in the geochemical model of granitoids formation. According to this model, the temperature of the beginning of the melt crystallization (Tmodel) was taken as the temperature of the apatite and zircon saturation. Therefore, Y content in coexistent apatite and zircon grains at the first stage of melt crystallization were estimated for each sample by means of extrapolation of the experimental graphs Ap Y C , Zm Y C vs. H to H = 0 (H is the grain mass determined by milliprobe single-grain XRF, while Y content determination in each grain). Comparison of the corresponding temperatures obtained via the calibrated Ap Zrn Y ln K vs. 1T dependence with Tmodel values demonstrates their tolerable agreement. This fact confirms the geochemical model of the first stage of the granitoid formation. Similar results for the following magmatic and magmatic-hydrothermal ore-forming events may be obtained by means of other assemblages (Zrn-Mnz, Zrn-Xnt, Zrn-Fl etc.).
Keywords: zircon; apatite; fluorite; monazite; xenotime; yttrium; trace elements; distribution coefficient; crystallization temperature; geochemical modeling